2020
DOI: 10.3390/s20164381
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Low-Cost Particulate Matter Sensors in Beijing

Abstract: Numerous particulate matter (PM) sensors with great development potential have emerged. However, whether the current sensors can be used for reliable long-term field monitoring is unclear. This study describes the research and application prospects of low-cost miniaturized sensors in PM2.5 monitoring. We evaluated five Plantower PMSA003 sensors deployed in Beijing, China, over 7 months (October 2019 to June 2020). The sensors tracked PM2.5 concentrations, which were compared to the measurements at the national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The AQY1 user guide mentioned that this effect is corrected for by way of a humidity correction algorithm; however, we still observed that the precision of the low-cost sensors decreased as RH increased; an effect which was more prominent in the calibrated datasets, and which may have been larger had there been no control for it by the manufacturer. Other studies [40] suggested an overestimation of particle concentrations when RH is high, potentially explained by the operational nature of optical particle counters and the detection and interpretation of water droplets as PM [17,20,41,42]. There are, however, studies showing negligible effects of meteorological variables on PM readings [10,16], and that the biases to RH and Temp varied across each sensor model and node; demonstrating that each sensor response is unique [10], as we found.…”
Section: Discussionsupporting
confidence: 60%
“…The AQY1 user guide mentioned that this effect is corrected for by way of a humidity correction algorithm; however, we still observed that the precision of the low-cost sensors decreased as RH increased; an effect which was more prominent in the calibrated datasets, and which may have been larger had there been no control for it by the manufacturer. Other studies [40] suggested an overestimation of particle concentrations when RH is high, potentially explained by the operational nature of optical particle counters and the detection and interpretation of water droplets as PM [17,20,41,42]. There are, however, studies showing negligible effects of meteorological variables on PM readings [10,16], and that the biases to RH and Temp varied across each sensor model and node; demonstrating that each sensor response is unique [10], as we found.…”
Section: Discussionsupporting
confidence: 60%
“…We designed two versions of motherboards for imported and domestic sensor boards, which also hold other sensors. The motherboard is connected to a microprocessor named BeagleBone Green Wireless (BBGW) through general-purpose input/output (GPIO) pins [ 38 ], and meteorological data, including temperature and relative humidity (RH), were collected from the Adafruit BME280 sensor. All data were collected with a time resolution of 2 s, then stored in the microprocessor and later uploaded to a remote server through the IoT, and data were also stored in a built-in secure digital memory (SD) card daily for backup.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the GP2YX was selected for use in the low-cost multimodal device, but initial testing with the GP2YX produced erratic and highly inaccurate data. Alternatively, PlanTower sensors are often used in many commercial devices [48] and have been found to report data that correlates with reference equipment when measuring PM2.5 [49]- [51]. Therefore, a (PlanTower) PMSA003 (Table 1) sensor was selected here to measure PM2.5.…”
Section: Low-cost Ieq Sensingmentioning
confidence: 99%